A large amount of microscopic precipitates are inevitably injected during infusion therapy without an in-line filter. Issue 2 (19th February 2022) - Shimoyama, Shinya; Takahashi, Daisuke; Arai, Syuhei; Asami, Yuji; Nakajima, Kimiko; Ikeda, Kentaro; Takizawa, Takumi; Kobayashi, Tomio
ABSTRACT: Infusion route problems can have a significant impact on hemodynamics in children with severe heart failure. Here, we report the case of a 13-year-old girl with dilated cardiomyopathy. Her condition fluctuated due to frequent occlusion of the central venous catheter (CVC) route. However, a quick check revealed no apparent abnormalities in the CVC, infusion route, in-line filter or infusion pump. Scanning electron microscopy revealed that dobutamine and heparin had crystallized and that the in-line filter membrane was occluded. This case emphasizes the importance of proper infusion route management in pediatric patients with severe heart failure. Even drugs that are used daily may form microscopic crystals at several concentrations and administration rates. Without an in-line filter, microscopic particles are injected into the body, and there is no evidence that the injected crystals do not cause permanent damage.